Effect of Guanosine 5-Monophosphate Supplementation to Flaxseed Oil-Based Diet on Growth and Intestinal Morphology of Juvenile Nile Tilapia (Oreochromis sp.) - Septiyani, Anita; Ridwanudin, Asep; Pangestu, Lintang Dion; Mahariawan, I Made Dedi; Nurdiani, Rahmi; Hariati, Anik Martinah (Trends in Sciences, 2025)
Suboptimal feed utilization efficiency and feed containing low nutrients are aquaculture problems. Many studies have demonstrated that nucleotides contribute for growth and gut health. Guanosine 5’-monophosphate with flaxseed oil combination can enhance feed efficiency and nutrient absorption. There does not seem to be a study that looks at how GMP and flaxseed oil work together to improve the growth and intestinal morphology juvenile Nile tilapia. The purpose of the research was to evaluate the effect combination of GMP supplementation and flaxseed oil at an appropriate dose on growth, intestinal structure (villous width), feed efficiency, and digestive enzyme activity in tilapia (Oreochromis sp.) juveniles. Juvenile Nile tilapia with an initial mean body weight of 1.42 ± 0.12 g and a shell length of 4.45 ± 0.12 cm were employed in this experimental study. Fish were fed 3% of their total body weight per day and kept in rectangular tanks at a density of 20. In addition to controls of flaxseed oil (LO) and fish oil (FO), juvenile fish were provided diets containing 0.2% (L-0.2) and 0.4% (L-0.4) GMP, alongside controls of flaxseed oil (LO) and fish oil (FO). After eight weeks, the findings showed that fish fed a diet enriched with 0.2% GMP (L-0.2) and flaxseed oil had improved final body weight, AGR, and SGR. Additionally, fish fed the L-0.2 than other diets. Thus, our study indicates that the inclusion of GMP in a flaxseed oil-based diet improves growth performance, intestinal villus height, and digestive enzyme activities. HIGHLIGHTS Nile tilapia were fed a diet based on flaxseed oil supplemented with guanosine 5’-monophosphate (GMP). The addition of GMP considerably enhanced the growth performance of juvenile Nile tilapia. Increased intestinal villi height and surface area were seen in fish fed diets supplemented with GMP. GMP may mitigate the adverse effect of plant oil-based diets on gut morphology. Dietary GMP can be a potential functional additive in aquafeeds replacing fish oil. GRAPHICAL ABSTRACT